LncRNA H19 promotes adipogenic differentiation disorder by sponging miR-130b-3p to upregulate PPARγ in steroid-induced osteonecrosis of the femoral head - Lin, Feifei; Yi, Min; Zhou, Shicheng; Wang, Qingyu (Frontiers in Genetics, 2025)
Steroid-induced osteonecrosis of the femoral head (SONFH) is a debilitating condition linked to glucocorticoid-induced adipogenic dysregulation of bone marrow mesenchymal stem cells (BMSCs). While long noncoding RNA H19 has been implicated in differentiation disorders across pathologies, its role in SONFH remains undefined. This study investigated H19’s regulatory mechanism in SONFH progression. We observed significant upregulation of H19 in both femoral head lesions and BMSCs from SONFH patients compared to controls. Knockdown of H19 in SONFH-derived BMSCs suppressed peroxisome proliferator-activated receptor γ (PPARγ) expression, attenuated adipogenic differentiation, and reduced lipid accumulation, as evidenced by decreased Oil Red O staining and FABP4 levels. Mechanistically, H19 acted as a competitive endogenous RNA (ceRNA) by sponging miR-130b-3p, thereby alleviating miR-130b-3p–mediated repression of PPARγ. Luciferase assays confirmed direct binding between miR-130b-3p and H19/PPARγ, while rescue experiments demonstrated that miR-130b-3p inhibition reversed PPARγ downregulation induced by H19 silencing. Our findings reveal a novel H19/miR-130b-3p/PPARγ axis driving adipogenic differentiation of BMSCs in SONFH, positioning H19 as a potential therapeutic target. This study provides critical insights into the epigenetic regulation of BMSC lineage commitment in SONFH pathogenesis, offering new avenues for intervention.